Alcoa & the auto industry - Rosenthal, Jean W., 1945-; Gentry, Bradford S.; Cort, Todd; Rogan, Jennifer Oldham; Elias, Jaan ([London] : SAGE, 2016)
Alcoa scored a major success with Ford's F-150. Could the company replicate its success to sell increasing amounts of aluminum to the automotive industry?
Originally Published in: Rosenthal, J., Gentry, B., Cort, T., Oldham Rogan, J., & Elias, J. (2014). Alcoa & the Auto Industry. New Haven, CT: Yale School of Management, Yale University. Retrieved from https://vol11.cases.som.yale.edu/alcoa-auto-industry.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; Aluminum Company of America; Consumer behavior -- Case studies; Economic forecasting -- Case studies; Marketing -- Management -- Case studies; Automobile industry and trade -- United States -- Management -- Case studies